The analysis potential of saline tilapia (Oreochromis niloticus) as a primary commodity candidate for silvofishery culture - Ariadi, Heri; Soeprapto, Hayati; Sulistiana, Ana (AGROMIX, 2025)
Introduction: Silvofishery is an innovative environmentally friendly aquatic cultivation concept that is currently widely developed in coastal areas with various cultivation commodities. The purpose of this research is to analyze the feasibility of saline tilapia (Oreochromis niloticus) as a biological, ecological, and financial commodity for silvofishery cultivation. Methods: This research method utilized a causal ex-post facto design on four silvofishery ponds. The parameters studied include water quality, biological parameters of fish, plankton abundance, and financial feasibility parameters of the business. Results: The research results show that the weight of saline tilapia ranged from 3.01 to 21.24 gr/fish (13.37 ± 6.53) and biomass growth ranged from 3.010 to 19.116 kg (12.886 ± 7.79). Silvofishery water quality parameters resulted in pH data of 7.8-8.2 (8.0 ± 0.14), dissolved oxygen of 4.01-5.92 mg/L (4.90 ± 0.55), temperature of 31.00-32.75°C (31.80°C ± 0.60), salinity of 5-8 gr/L (6.3 ± 1.28), and organic matter of 54.32-73.87 mg/L (62.90 ± 6.33). Plankton abundance ranged from 10,000 to 90,000 cells/ml with the dominance of the genus Chlorella sp. The business feasibility analysis results showed a profit value of Rp. 8,840,000,-, R/C Ratio of 1.55, BEP unit of 297 kg, BEP sales of Rp. 4,428,000,-, profitability of 25%, Net Present Value of Rp. 101,528,000,-, IRR of 20.45%, and payback period of 2.7 years. This means that based on growth performance, pond water quality conditions, and business profit levels, the use of saline tilapia commodities in silvofishery pond cultivation is highly recommended. Conclusion: The conclusion of this research is that saline tilapia commodities are highly suitable when used as a primary cultivation in integrated and comprehensive silvofishery activities.